Co-evolution of fish and rice farming by Austroasiatic communities in the Neolithic Era and early documentation of aquaculture in China - Edwards, Peter (Frontiers in Aquaculture, 2025)
This paper is a review of the co-evolution of fish and rice farming about 10,000 years ago in the early Neolithic Era in China. China is often referred to as the origin of fish farming based on an oft cited document of Fan Li (448 BC – 536 BC) about 2,500 years ago. It is the earliest account of farming common carp (Cyprinus carpio) but its origin dates back much further. Oracle bone scripts of the Shang Dynasty (1,046 BC – 1,600 BC) are the earliest written record of fish farming in ponds. Farming common carp was prohibited in the Tang Dynasty (618 AD-907 AD) because the name of the fish, Li, was the same as that of an emperor, and this possibly led to farming Chinese carps in polyculture. There were increases in temperature and rainfall at the end of the last ice age in the Yangtze River Basin during the early Neolithic Era about 8,000 BC, drivers for subsequent development. A vast freshwater environment of inland lakes and swamps developed, with wetland plants including wild rice, as well as fish, bordered by deciduous forests and semi-arid grasslands on higher land. This enabled Austroasiatic people to gather wild foods, terrestrial and aquatic nuts as well as fish and rice. A mixed economy of hunting, gathering and fishing evolved into the co- evolution of fish and rice farming.